Integrated land management: a need for providing speedy service to the stake holders - Bhuiyan, Md. Zahidul Islam (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.